Does body mass index (BMI) significantly influence aseptic loosening in primary total knee arthroplasty? Insights from a long-term retrospective cohort study - Mohammad Ayati Firoozabadi; Amir Hossein Mafi; Sina Afzal; Shahabaldin Beheshti Fard; Homayoon Khaledian; Ali Bozorgsavoji; Sina Azadnajafabad; Seyed Mohammad Javad Mortazavi (BMC Musculoskeletal Disorders)
Abstract Background Total knee arthroplasty (TKA) offers substantially improved function for patients with severe osteoarthritis, but long-term success can be overshadowed by aseptic loosening, a complication with a multifactorial etiology. This study aims to investigate the association between BMI and the rate of aseptic loosening and other complications in patients undergoing primary TKA. Methods This retrospective cohort study examined 354 TKA patients, evenly categorized by BMI (≤ 30 kg/m² and > 30 kg/m²). Demographics, imaging findings, surgical details, and postoperative complications were assessed. Survival for postoperative complications was compared between the two BMI cohorts using Kaplan-Meier analysis. Results The mean age of patients in the BMI ≤ 30 group was 62.44 years, while it was 62.84 years in the BMI > 30 group. The number of patients with short-stemmed tibial components was comparable in the two groups. Out of the total patients, 350 cases showed no loosening, while four experienced aseptic loosening. There was no statistically significant difference in the rate of aseptic loosening or other complications between the two groups. Conclusion While a high BMI may contribute to aseptic loosening, it does not appear to be the sole determinant. A multifactorial approach to prevention and management is essential, considering patient-specific factors and prosthetic considerations. Future research with larger cohorts and extended follow-up periods is needed to better elucidate the interplay between BMI and aseptic loosening in patients undergoing TKA.